Diagnostic Dilemma in Massive Cellular Leiomyoma with Cystic Degeneration - Arya Ady Nugroho; Riyan Hari Kurniawan; Aprilia Asthasari Siregar (PT Dexa Medica, 2025)
Background: Uterine leiomyomas, commonly known as fibroids, are prevalent benign tumors in women of reproductive age. While often asymptomatic, they can become symptomatic when they enlarge or when degenerative changes occur. Cystic degeneration, which occurs in approximately 4% of leiomyomas, presents a diagnostic challenge, as it can mimic malignancy on imaging due to its solid-cystic appearance on imaging. This case report aims to highlight the diagnostic dilemma posed by large leiomyomas with cystic degeneration and to emphasize the importance of advanced imaging as well as histopathological examination in confirming benign diagnoses and excluding malignancy. Case Presentation: A 27-year-old woman presented with progressive abdominal distension and intermittent lower abdominal pain over thepast year. Imaging revealed a large, solid-cystic mass in the uterine fundus, raising suspicion of malignancy. Further diagnostic workup, including magnetic resonance imaging (MRI) and histopathological examination, confirmed the massas a benign leiomyoma with cystic degeneration. The patient underwent a laparotomy myomectomy, and intraoperative findings confirmed a well-circumscribed subserosal mass with cystic degeneration. Histopathology examination alsoconfirmed a benign leiomyoma, ruling out malignancy. Conclusion: This case underscores the diagnostic challenges of differentiating large leiomyomas with cystic degeneration from malignancies. Advanced imaging, particularly MRI, along with histopathological examination, plays a crucial role in establishing an accurate diagnosis and subsequently, guiding appropriate management.